Protist distribution in the Western Fram Strait in summer 2010 based on 454-pyrosequencing of 18S rDNA - Kilias, Estelle; Wolf, Christian; Nöthig, Eva-Maria; Peeken, Ilka; Metfies, Katja (Journal of phycology, 2013)
In this study, we present the first comprehensive analyses of the diversity and distribution of marine protist (micro‐, nano‐, and picoeukaryotes) in the Western Fram Strait, using 454‐pyrosequencing and high‐pressure liquid chromatography (HPLC) at five stations in summer 2010. Three stations (T1; T5; T7) were influenced by Polar Water, characterized by cold water with lower salinity (<33) and different extents of ice concentrations. Atlantic Water influenced the other two stations (T6; T9). While T6 was located in the mixed water zone characterized by cold water with intermediate salinity (~33) and high ice concentrations, T9 was located in warm water with high salinity (~35) and no ice‐coverage at all. General trends in community structure according to prevailing environmental settings, observed with both methods, coincided well. At two stations, T1 and T7, characterized by lower ice concentrations, diatoms (Fragilariopsis sp., Porosira sp., Thalassiosira spp.) dominated the protist community. The third station (T5) was ice‐covered, but has been ice‐free for ~4 weeks prior to sampling. At this station, dinoflagellates (Dinophyceae 1, Woloszynskia sp. and Gyrodinium sp.) were dominant, reflecting a post‐bloom situation. At station T6 and T9, the protist communities consisted mainly of picoeukaryotes, e.g., Micromonas spp. Based on our results, 454‐pyrosequencing has proven to be an adequate tool to provide comprehensive information on the composition of protist communities. Furthermore, this study suggests that a snap‐shot of a few, but well‐chosen samples can provide an overview of community structure patterns and succession in a dynamic marine environment.